2009
DOI: 10.1016/j.jacc.2009.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women With Dilated Cardiomyopathy

Abstract: In pregnant women with DCM the risk of adverse cardiac events is considerable, and pre-pregnancy characteristics can identify women at the highest risk. Pregnancy seems to have a short-term negative impact on the clinical course in women with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 21 publications
4
89
1
4
Order By: Relevance
“…(Prebitero et al, 2009) In a study on pregnancy in patients with dilated cardiomyopathy, an OR of 43 was found for moderate or severe left ventricular dysfunction and 39% of the pregnancies where complicated. (Grewal et al, 2009) Risk factors for adverse events were moderate (EF 30%-44%) or severe (EF<30%) ventricular dysfunction and NYHA class III or IV at baseline or prior cardiac event. Compared with non-pregnant patients with dilated cardiomyopathy, pregnant patients needed more medication and adverse cardiac events were more common.…”
Section: A 41 Year Old Patient Presented To the Out Patient Departmenmentioning
confidence: 98%
“…(Prebitero et al, 2009) In a study on pregnancy in patients with dilated cardiomyopathy, an OR of 43 was found for moderate or severe left ventricular dysfunction and 39% of the pregnancies where complicated. (Grewal et al, 2009) Risk factors for adverse events were moderate (EF 30%-44%) or severe (EF<30%) ventricular dysfunction and NYHA class III or IV at baseline or prior cardiac event. Compared with non-pregnant patients with dilated cardiomyopathy, pregnant patients needed more medication and adverse cardiac events were more common.…”
Section: A 41 Year Old Patient Presented To the Out Patient Departmenmentioning
confidence: 98%
“…It has generally a family history and can rapidly deteriorate during pregnancy due to hemodynamic load. 15,69 Women with dilated cardiomyopathy should be advised about maternal risk, especially when LVEF is <40% and should be suggested to terminate if LVEF is under 20%. In case of mother's refuse, it is necessary for her to be followed up by a tertiary center with a multidisciplinary team.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…31 An analysis of adverse outcomes during pregnancy in women with DCM revealed that there were no adverse events in women with none of these 3 clinical parameters (moderate or severe LV dysfunction, NYHA functional class III or IV, and/or a previous cardiac event). 32 In clinical practice, asymptomatic women with mild DCM mostly tolerated pregnancy well. Therefore, it is reasonable to surmise PPCM-specific factors, such as angiogenic imbalance, also affect many women with a positive genetic background of DCM and aggravate the condition.…”
Section: Ppcm and Hypertensive Disordersmentioning
confidence: 99%